CD25 targeting with the afucosylated human IgG1 antibody RG6292 eliminates regulatory T cells and CD25+ blasts in acute myeloid leukemia - Pousse, Laurène; Korfi, Koorosh; Medeiros, Bruno C.; Berrera, Marco; Kumpesa, Nadine; Eckmann, Jan; Hutter, Idil Karakoc; Griesser, Vera; Karanikas, Vaios; Klein, Christian; Amann, Maria (Frontiers in Oncology, 2023)
Background Acute Myeloid leukemia is a heterogeneous disease that requires novel targeted treatment options tailored to the patients’ specific microenvironment and blast phenotype. Methods We characterized bone marrow and/or blood samples of 37 AML patients and healthy donors by high dimensional flow cytometry and RNA sequencing using computational analysis. In addition, we performed ex vivo ADCC assays using allogeneic NK cells isolated from healthy donors and AML patient material to test the cytotoxic potential of CD25 Mab (also referred to as RG6292 and RO7296682) or isotype control antibody on regulatory T cells and CD25+ AML cells. Results Bone marrow composition, in particular the abundance of regulatory T cells and CD25 expressing AML cells, correlated strongly with that of the blood in patients with time-matched samples. In addition, we observed a strong enrichment in the prevalence of CD25 expressing AML cells in patients bearing a FLT3-ITD mutation or treated with a hypomethylating agent in combination with venetoclax. We adopted a patient-centric approach to study AML clusters with CD25 expression and found it most highly expressed on immature phenotypes. Ex vivo treatment of primary AML patient samples with CD25 Mab, a human CD25 specific glycoengineered IgG1 antibody led to the specific killing of two different cell types, CD25+ AML cells and regulatory T cells, by allogeneic Natural Killer cells. Conclusions The in-depth characterization of patient samples by proteomic and genomic analyses supported the identification of a patient population that may benefit most by harnessing CD25 Mab’s dual mode of action. In this pre-selected patient population, CD25 Mab could lead to the specific depletion of regulatory T cells, in addition to leukemic stem cells and progenitor-like AML cells that are responsible for disease progression or relapse.